2019
DOI: 10.1039/c9ra01550g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of structure regulation of hyper-branched polyester modified carbon nanotubes on toughening performance of epoxy/carbon nanotube nanocomposites

Abstract: Carboxylic carbon nanotubes were modified by a series of hyperbranched polyesters (HBP), and epoxy resin/carbon nanotubes composites were prepared. The effect of structure regulation of HBP on toughening properties of composites was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The hydrogen bond is an interaction formed between two highly electronegative atoms through hydrogen atoms as the media, which plays an important role in the mechanical properties and aging resistance of polymers [ 23 ]. Furthermore, it can be expressed as X-H···Y, where X and Y are usually denoted as the donor and acceptor atoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen bond is an interaction formed between two highly electronegative atoms through hydrogen atoms as the media, which plays an important role in the mechanical properties and aging resistance of polymers [ 23 ]. Furthermore, it can be expressed as X-H···Y, where X and Y are usually denoted as the donor and acceptor atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperbranched polyester is a kind of highly branched three-dimensional dendritic polyester which can be used as an effective surface modifier to control the inorganic–organic interface between filler and polymer matrix [ 15 , 19 , 20 ]. Many active terminal functional groups of hyperbranched polyester grafted on nanoparticles can interact closely with the polymer matrix, acting as a bridge between the two interfaces, which leads to better dispersibility of fillers and interaction bonding to improve the performance of composite [ 21 , 22 , 23 , 24 ]. However, many studies concentrate on the traditional experimental tests, which have difficulty articulating internal mechanisms clearly.…”
Section: Introductionmentioning
confidence: 99%
“…Zang and Glukhova studied the formation of the T-shaped junction between Another type of approach to attain branched CNTs is based on the covalent or noncovalent functionalization with branched or dendritic structures to connect the CNTs with each other. The most commonly used procedures rely on grafting onto the CNTs with branched or dendritic polymers [19][20][21]. However, covalent functionalization is well-known to affect the electronic properties of CNSs and requires careful monitoring to preserve the CNS [22].…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…Researchers have found that branched CNSs significantly enhance the mechanical, electrical, and thermo-conductive properties in a wide range of nanocomposites. Branched MWCNT fillers form stronger networks by comparison with conventional MWCNTs, leading to enhanced mechanical performance of the resulting materials [13,19,21,[115][116][117][118]. Natural catalysts can be used to fabricate branched MWCNTs as reinforcement materials to enhance the mechanical and electrical properties of composites.…”
Section: Composite Performance Enhancementmentioning
confidence: 99%
See 1 more Smart Citation